Demo: A Versatile Controller Concept for Mobile Gaming - Helmes, John; Taylor, Stuart; Hodges, Steve; Lovett, Chris (UbiComp 2018: Extended Abstracts, 2018)
Popular games for smartphones and tablets focus on touchscreen-based interaction. Here we describe a speculative research exploration motivated by the desire to enable traditional gaming experiences on mobile devices by incorporating tactile input controls. The design and ergonomics of our prototype accessory concept were informed by anecdotal feedback from a variety of gamers.